RBNCANA BISNIS UNTUK USAHA JASA CUCI SALON MOBIL ''SURYA OTO CARE'' - , Mochamad Brian Adam, Sudiyanti, SE., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Car Wash and car saloon business is growing rapidly nowadays in several city in Indonesia and also in Banjarnegara. But that growing sometimes not in line with the good quality and service. Sometimes, business player only give the services that has been known by society and lack of innovation also lack of comfort in washing. This research aim to make a business planning with better in using some functional analysis so later on can be used as a basic in fulfilling the necessity of quality and comfortness in washing and also creating an innovation of competitive advantage. Than from the result of this research showing that car wash and saloon business is having worthiness to be run because from the financial projection finding showed that this business is profitable and this business planning also made to be a guidance for investors and entrepreneur.